2017
DOI: 10.1039/c7nr04962e
|View full text |Cite
|
Sign up to set email alerts
|

An engineering approach to synthesis of gold and silver nanoparticles by controlling hydrodynamics and mixing based on a coaxial flow reactor

Abstract: In this work we present a detailed study of flow technology approaches that could open up new possibilities for nanoparticle synthesis. The synthesis of gold and silver nanoparticles (NPs) in a flow device based on a coaxial flow reactor (CFR) was investigated. The CFR comprised of an outer glass tube of 2 mm inner diameter (I.D.) and an inner glass tube whose I.D. varied between 0.142 and 0.798 mm. A split and recombine (SAR) mixer and coiled flow inverter (CFI) were further employed to alter the mixing condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 70 publications
(84 reference statements)
0
36
0
Order By: Relevance
“…Then alloy NPs, with 32 ± 2 nm diameter, were synthesized, which can be used as seeds for the next growth stage. NaCit was added before metal salts in order to adjust the pH to slow down the chemical reduction velocity, thus facilitating homogeneous growth of NPs . For following growth stage(s), NPs synthesized in the last stage were used as seeds, and a similar process was performed to obtain the designed bioimaging labels.…”
Section: Methodsmentioning
confidence: 99%
“…Then alloy NPs, with 32 ± 2 nm diameter, were synthesized, which can be used as seeds for the next growth stage. NaCit was added before metal salts in order to adjust the pH to slow down the chemical reduction velocity, thus facilitating homogeneous growth of NPs . For following growth stage(s), NPs synthesized in the last stage were used as seeds, and a similar process was performed to obtain the designed bioimaging labels.…”
Section: Methodsmentioning
confidence: 99%
“…Total flow rate (mL min -1 ) and τ (min) The effect of the total flow rate was firstly investigated in view of its proved effects on the fluidodynamics of the nanoprecipitation. 13,27 Indeed, at low flow rates the regime is almost laminar (low Reynolds number) while it becomes turbulent at higher flow rates. A compromise between nucleation, which is facilitated by laminar mixing and low flow rates, and growth that occurs mainly at longer residence time (τ) is needed for an efficient FNP process.…”
Section: Variable Valuesmentioning
confidence: 99%
“…A compromise between nucleation, which is facilitated by laminar mixing and low flow rates, and growth that occurs mainly at longer residence time (τ) is needed for an efficient FNP process. 13,27 The effect of the flow rate was investigated by using a 0.5% (w/v) aqueous solution of D-leucine, a 10 mL mesoreactor coil with 1 mm of internal diameter (ID) and a three-way mixer with Y-geometry, according to the flow set-up depicted in Fig. 1.…”
Section: Variable Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…For gold and silver nanoparticles synthesis, Baber et al demonstrated the potential of using microfluidic reactor with a coaxial flow in controlling nanoparticle size and dispersity. Experimental studies on segmented flow have shown that it was highly influential in the synthesis of nanoparticles due to its flexibility in manipulation of mass transfer and hydrodynamics characteristics .…”
Section: Introductionmentioning
confidence: 99%